Fragmentation Pattern and Removal Mechanism of Concrete Subjected to Abrasive Water Jet Impact - Jialiang Liu; Yujie Zhu; Yongzhi Xue; Hao Sun (Advances in Materials Science and Engineering)
Abrasive water jet (AWJ) breaking technology is suitable for the maintenance and repair of concrete structures, generating minimal dust, low tool wear, and no vibrations or selective destruction. The failure features and mechanisms of concrete subjected to AWJ impact are fundamental issues of AWJ breaking technology, which are also related to the safety and quality of engineering construction. Based on computed tomography (CT), scanning electron microscopy (SEM), and image processing technology, this paper studied the fragmentation pattern and removal mechanism of concrete under AWJ impact. The general failure characteristics and crack propagation law of concrete subjected to AWJ impact were described through AWJ impact concrete tests. The spatial distribution of damage in concrete subjected to AWJ impact can be divided into the intensive action zone, the transition zone, and the weak action zone. The removal mechanism of AWJ was discussed by comparing the impact performance of a pure water jet (PWJ) system. The results indicate that abrasive particles can cause cliff-shaped fracture and lip-shaped distortion in the aggregate part and flat fracture surface in the matrix part. There is no obvious crack in the interfacial transition zone (ITZ) due to the weakening of the water wedge effect.